3 Long term follow-up after stent implantation following patch repair of aortic coarctation. (June 2018) - Straw, Sam; Thomson, John; Bentham, Jamie
Abstract : Introduction: Aortic coarctation is most commonly diagnosed in infancy or childhood, with patients subsequently undergoing repair using a variety of surgical techniques. During the 1970s/1980s coarctation repair was often performed using a synthetic patch (usually Dacron or similar) to augment the narrowed aorta. Such repairs have been shown to be susceptible to aneurysm formation due to separation of the patch from native aortic tissue. As a result, there can be reluctance to perform angioplasty or stent insertion for recurrent coarctation or aneurysm formation, for fear of dehiscence. Data on the procedural risks of transcatheter re-intervention and long-term follow up into adult life is lacking for such patients. Methods: Eleven patients were identified from our adult congenital heart disease database who had undergone stent insertion following coarctation patch repair in childhood. Ten patients were male, one female, mean age at initial repair was 3 years±3.55. For 8 patients, the initial operation was patch repair, whilst in five the patch augmentation had been undertaken after an unsatisfactory initial subclavian flap repair. In all cases the indication for re-intervention was recurrence of stenosis at the site of repair in association with systemic hypertension. Results: Mean age at stent implantation was 21.3 years±8.59, median time from patch repair to stent insertion was 17 years (10.5–20). Stent insertion was technically successful in all cases with no acute complications, in particular there was no acute aortic rupture or aneurysm formation. Median pressure gradient reduction was 15 mmHg (12.1–20), 0<0.0001. Mean follow up was 7.09 years, at analysis 10 patients were under active follow up (one patient had moved abroad) and all patients were alive. In nine out of ten cases, cross sectional imaging at late follow-up demonstrated no aneurysm or evidence of aortic wall complication. One case had a minor pre-existing arch aneurysm that pre-dated the stent insertion and did not progress on cross-sectional imaging. One patient required re-intervention for a new aneurysm at the distal end of the transverse arch after six years, following deployment of an uncovered stent into the transverse arch at age of 17, and underwent thoracic endovascular aortic repair. Two patients underwent successful subsequent stent dilation following initial insertion, without complications and with resolution of residual gradient. Implications: Previous patch repair is regarded as high risk for re-intervention, however the case series presented demonstrates that there were no immediate complications associated with stent treatment. Only one late complication, in a patient who had multiple procedures to their aortic arch occurred, and this was successfully treated.